Depth distribution of plant-parasitic nematodes on bentgrass golf greens in Missouri and Indiana - McCurdy Asa L.; Barizon Jefferson; Miller G.L. (Journal of Nematology)
Control of plant-parasitic nematodes (PPNs) on golf putting greens with nematicides is dependent on the seasonal occurrence and depth distribution of target PPN populations. This study aimed to determine if plant-parasitic nematode populations on golf course putting greens in Missouri and Indiana peaked at a targetable depth at a specific time in the year, focusing primarily on lance (Hoplolaimus spp.) and root-knot (Meloidogyne spp.) nematodes. To elucidate species diversity in the region, rDNA from a subset of lance and root-knot nematodes was sequenced and analyzed, with additional micromorphology of a lance nematode assessed in scanning electron micrographs (SEM). Soil samples were taken to a depth of 25 cm and stratified into 5 cm increments during April, June, August and October at seven sites across Missouri, three in the Kansas City metro of Kansas in 2021 and in ten sites across Indiana in 2022. Samples were stratified in five-centimeter increments and aggregated for a total of 100 cm3 of soil at each depth for each sampling. Samples were processed using a semi-automatic elutriator followed by the sucrose-flotation method, and populations were counted using a hemocytometer and recorded. For molecular characterization, rDNA was extracted and analyzed from 31 individual lance nematodes from one site in Missouri and eight sites in Indiana, and 13 root-knot nematodes from nine sites across Indiana. A significant interaction occurred between sampling month and depth for lance and ring nematodes Missouri/KS, with both PPN populations peaking at the 0–5 cm depth during October, which is well after most targeted nematicide applications are applied. Ring nematodes in Indiana did not follow this trend and were most abundant in August at a depth of 0–5 cm. No significant interaction between depth and month occurred for lance or root-knot nematodes in Indiana, or root-knot nematodes in Missouri/KS. Hoplolaimus stephanus and H. magnistylus were the lance species identified on golf greens, and Meloidogyne naasi, M. graminicola and M. marylandi were the root-knot species identified. Scanning-electron micrographs confirmed morphological characteristics unique to H. stephanus.